Investigating The Nexus Between Manpower Development Programmes and Employee’s Performance in Local Government Service Commission, Taraba State, Nigeria - Thomas Daniel Maiyanga; Danladi Hussaini; Nwosu Chinedu Everest (Research Parks Publishers, 2024)
This study investigates the nexus between manpower development programmes and employee’s performance in Local Government Service Commission, Taraba State, Nigeria. With the aid of the study objectives, two hypotheses were formulated in the study. A sample size of 131 was adopted for the study. The purposive sampling technique was used to select the entire population of the study due to its’ convenient in the conduct of the research. The summation of all the responses was presented using frequency distribution tables and simple percentages. In addition, the mean analysis was used to analyze the data generated from the field while the chi-square statistical tool was employed to test the hypotheses formulated in the study. The test statistics reveals among others that manpower development programmes in the form of in-service training and workshops and seminars have impact or influence on employee’s productivity and job knowledge as an aspect of employee’s performance in Local Government Service Commission, Taraba State. The study recommends among others that, since manpower development programme in the form of in-service training has impact on employee’s productivity in Local Government Service Commission, Taraba State. Taraba State government should continue to ensure that the employees in Local Government Service Commission are subjected for in-service training. By so doing, the employees will acquire additional skills and values required which in turn increases their productivity at work.